2019
DOI: 10.4049/jimmunol.1801686
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF Synthesized by CD4 T Cells Modulates Allergic Airway Eosinophilia by Regulating IL-5 Synthesis

Abstract: CD4 T cells express the epidermal growth factor (EGF) receptor ligand, heparin-binding EGF (HB-EGF), with no defined immuno-pathophysiological function. Therefore, we wished to elucidate the function of HB-EGF synthesized by CD4 T cells in the context of allergic pulmonary inflammation and the asthma surrogate, airway hyperresponsiveness, in a murine acute model of asthma. In this study, we show how knocking out HB-EGF expression in CD4 T cells in vivo attenuates IL-5 synthesis in the lung that is accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Similar to NGF and other neurotrophins, HB-EGF is synthesized in a premature transmembrane form (pro-HB-EGF) before it is cleaved by numerous metalloproteinases (MMP3, MMP9, ADM9, ADAM10, ADAM12, ADAM17) into its mature, soluble form (215). While the membrane anchored pro-HB-EGF functions as juxtacrine growth factor and receptor for diphtheria toxin in some species, soluble HB-EGF has recently been described to modulate cell migration, differentiation, and inflammatory functions in multiple cell types (216)(217)(218)(219)(220)(221)(222). In addition, HB-EGF enhances neurogenesis in models of ischemic injury and promotes the survival of dopaminergic neurons (223,224) (Figure 2).…”
Section: Hb-egfmentioning
confidence: 99%
“…Similar to NGF and other neurotrophins, HB-EGF is synthesized in a premature transmembrane form (pro-HB-EGF) before it is cleaved by numerous metalloproteinases (MMP3, MMP9, ADM9, ADAM10, ADAM12, ADAM17) into its mature, soluble form (215). While the membrane anchored pro-HB-EGF functions as juxtacrine growth factor and receptor for diphtheria toxin in some species, soluble HB-EGF has recently been described to modulate cell migration, differentiation, and inflammatory functions in multiple cell types (216)(217)(218)(219)(220)(221)(222). In addition, HB-EGF enhances neurogenesis in models of ischemic injury and promotes the survival of dopaminergic neurons (223,224) (Figure 2).…”
Section: Hb-egfmentioning
confidence: 99%
“…Therefore, the combination of HBEGF and adipose-derived stem cells may provide a new solution for the treatment of hair loss. Farahnak et al reported that the intrinsic HBEGF expressed by CD4 T cells had immunomodulatory functions in T(H)2 inflammation and airway dysfunction, 46 and the mechanism was mainly to regulate the expression of IL-5 by binding to and inhibiting the inhibitory function of Bcl-6. Yu et al reported that HBEGF prevented the apoptosis of stromal cells by enhancing the activities of antioxidant enzymes SOD, CAT and GPX, inhibiting the activity of Caspase-3 and the expression of Bax, and restoring the mRNA level of Bcl-2 to improve the oxidative stress-mediated decidua injury.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate lung function, we followed methods previously described 21,22 . Mice were sedated with xylazine (8 mg/kg; intraperitoneally) and anesthetized with pentobarbital sodium (30 mg/kg; intraperitoneally).…”
Section: Measurement Of Respiratory Mechanicsmentioning
confidence: 99%
“…BAL fluid processing and analysis were performed as previously published 22 . Following lung mechanics measurements, BAL was performed by instilling 1 mL of cold PBS via the tracheal cannula, with a subsequent recovery of approximately 0.8 mL of fluid by gentle suction.…”
Section: Bronchoalveolar Lavage (Bal) Fluid Analysismentioning
confidence: 99%